Cold-acclimation improves cold-tolerance of diabetic rats - Ferro, Jesus A; Macari, Marcos [UNESP]; Eizirik, Décio L (Elsevier, 1987)
1. 1. The aim of these experiments was to study the extent to which previous cold-acclimation improves the cold-tolerance of diabetic rats. 2. 2. Alloxan diabetic rats (fasting blood glucose higher than 200mg/dl) were used in the experiments. 3. 3. In Expt. 1, non-cold-acclimated control and diabetic rats were exposed to cold environment (7-9°C), and the percentage of survival calculated during a 12-day experimental period. In Expt. 2, the rats were previously cold-acelimated before alloxan or saline injection (diabetic and control cold-acclimated rats) and the survival rate was also assessed during a 12-day period in the cold. 4. 4. The percentage of survival of the non-cold-acclimated diabetic rats (Expt.l) was 19% compared with 79% of the diabetic cold-acclimated animals (Expt. 2). There were no deaths in the control groups. 5. 5. Cold-acclimated diabetic rats maintained a near-normal thermogenic response after noradrenaline injection. This response was impaired in non-cold-acclimated diabetic rats. 6. 6. The results of these experiments suggest that the enhanced cold-tolerance of diabetic cold-acclimated rats could be related to the increased sympathetic activity and enhanced insulin sensitivity in thermogenic tissues, such as brown fat. © 1987.
Keywords: noradrenalin; acclimatization; animal; body weight; cold; comparative study; drug effect; experimental diabetes mellitus; male; pathophysiology; rat; rat strain; reference value; thermoregulation; time; Acclimatization; Animal; Body Temperature Regulation; Body Weight; Cold; Comparative Study; Diabetes Mellitus, Experimental; Male; Norepinephrine; Rats; Rats, Inbred Strains; Reference Values; Support, Non-U.S. Gov't; Time Factors